2015
DOI: 10.4236/ojgas.2015.57013
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhoidal Disease in Cotonou: Epidemiological, Clinical and Anuscopic Aspects

Abstract: The haemorrhoidal disease is a very common disorder in proctology. It is favoured by many factors. Although benign, its treatment is difficult. Our aim is to study the epidemiological, clinical and anuscopic of haemorrhoidal disease. This was a cross sectional, descriptive and prospective study covering a three-month period from 06 January 2014 to 10 April 2014. It involved patients seen in gastroenterology consultation in internal medicine of the National Teaching Hospital of Cotonou and in the digestive dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The frequency of external hemorrhoidal thrombosis in recent births was 14.6%. This result is comparable to those of Sehonou et al [7] in Benin who found 14.8%. On the other hand, Abramovitz et al [8] in France found a higher frequency respectively of 20%.…”
Section: Discussionsupporting
confidence: 90%
“…The frequency of external hemorrhoidal thrombosis in recent births was 14.6%. This result is comparable to those of Sehonou et al [7] in Benin who found 14.8%. On the other hand, Abramovitz et al [8] in France found a higher frequency respectively of 20%.…”
Section: Discussionsupporting
confidence: 90%
“…The factors associated with co-infection in this study were history of blood transfusion, lack of immunization against hepatitis B, and duration of ART lower than five years. Other authors have also identified blood transfusion as associated with co-infection in Benin and Nigeria [22,23]. We can assume with the results in Table 5 that HIV infected children with history of blood transfusion are running 2.64 times risk of hepatitis.…”
Section: Discussionmentioning
confidence: 64%